Mesic, Julian C. [Berkeley Women's City Club Pool by Julian C. Mesic] - Julian C. Mesic (1889-1961)::::::::: (1933)
Illustration of the Berkeley Women's City Club indoor pool, by Julian C. Mesic. The estimated date is based off the note in the lower left corner "1/33."